INKLUSI DIGITAL DALAM IMPLEMENTASI SISTEM PEMERINTAHAN BERBASIS ELEKTRONIK (SPBE) DI KOTA SURABAYA - Berliana Mustika Rani (Journal Publicuho, 2025)
This study aims to analyse the form and effectiveness of digital inclusion policies in the implementation of SPBE in Surabaya City, focusing on efforts to reach vulnerable groups such as the elderly, persons with disabilities, and the digitally poor. This study applies a qualitative method with a case study approach. Data were collected through in-depth interviews, document review, and field observation involving local government actors and representatives of vulnerable groups. The analysis is guided by the frameworks of Digital Inclusion Theory, Digital Era Governance, and Policy Implementation Theory. The results show that the Surabaya City Government has initiated several digital inclusion policies, including free public WiFi, digital literacy training, and integrated service platforms. However, the implementation remains less effective due to limited infrastructure, low digital literacy levels, and a lack of sustainable support for vulnerable populations. This study concludes that the implementation of digital inclusion in SPBE is still partial and requires cross-sector collaboration and a long-term strategy to ensure that digital transformation does not deepen social inequality.